Wireless communications with energy harvesting devices - Ang, Jin Yan (2012)
In the world today, many unwanted energy is wasted either as heat or radiation though the transmission while the renewable energy technology is not new (e.g., solar and wind.). Energy harvesting sensors, which harvest energy from the environment, is an alternative for batteries used in wireless communication links.